APPLICATION OF PROBIOTIC IN THE NURSERY AND GROW-OUT OF (Clarias gariepinus) IN THE PANDANWANGI VILLAGE - Muhammad Fakhri; Muhammad Rasyid Fadholi; Pratama Diffi Samuel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Catfish (Clarias gariepinus) is one of the most cultured fish in Indonesia. The main problem in catfish culture is low productivity and high feed conversion ratio (FCR). The purpose of this activity was to evaluate the application of probiotic in catfish culture. For nursery, catfish juveniles with size of 2-3 cm was cultured for 40 days while fish with size of 7-9 cm was cultivated for 85 days in grow-out tank. All tanks were treated by probiotic during one culture cycle. Probiotic was directly given to the water and administered by feed. The results showed that survival rates of nursery and grow-out tanks were 90 and 92%, respectively. The FCR value in the grow-out was 0.8. It can concluded that probiotic application was able to improve the survival rate and the feed conversion ratio in catfish culture.